2017
DOI: 10.1044/2016_jslhr-s-16-0149
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Marker to Discriminate Childhood Apraxia of Speech From Speech Delay: IV. The Pause Marker Index

Abstract: Purpose: Three previous articles provided rationale, methods, and several forms of validity support for a diagnostic marker of childhood apraxia of speech (CAS), termed the pause marker (PM). Goals of the present article were to assess the validity and stability of the PM Index (PMI) to scale CAS severity. Method: PM scores and speech, prosody, and voice precision-stability data were obtained for participants with CAS in idiopathic, neurogenetic, and complex neurodevelopmental disorders; adult-onset apraxia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…We define a diagnostic marker of a disorder as "one or more operationalized and standardized signs with sensitivity to and specificity for persons with prior, present, and/or future expression of the disorder at estimated levels of accuracy." Some diagnostic markers may have only categorical properties (i.e., presence/absence of disorder), whereas markers that meet distributional criteria for ordinal or interval measurement levels may also be used to scale the severity of a disorder (see PM IV; Shriberg et al, 2017c). As defined herein, positive status for a conclusive behavioral diagnostic marker is the ideal inclusionary criterion on which researchers can base the identification and development of biomarkers for diseases or disorders.…”
Section: Definition Of Diagnostic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…We define a diagnostic marker of a disorder as "one or more operationalized and standardized signs with sensitivity to and specificity for persons with prior, present, and/or future expression of the disorder at estimated levels of accuracy." Some diagnostic markers may have only categorical properties (i.e., presence/absence of disorder), whereas markers that meet distributional criteria for ordinal or interval measurement levels may also be used to scale the severity of a disorder (see PM IV; Shriberg et al, 2017c). As defined herein, positive status for a conclusive behavioral diagnostic marker is the ideal inclusionary criterion on which researchers can base the identification and development of biomarkers for diseases or disorders.…”
Section: Definition Of Diagnostic Markersmentioning
confidence: 99%
“…A marker with such properties to use as the inclusionary criterion in CAS research requires psychometric support for its diagnostic accuracy and empirical support for its theoretical coherence with the speech processing deficits proposed to define CAS. The research reported in the present article (PM I), in PM II (Shriberg et al, 2017a), and in PM IV (Shriberg et al, 2017c) addresses the former needs, with findings in PM III (Shriberg et al, 2017b) assessing the latter need for theoretical coherence. The following review includes relevant terms and concepts in classification, speech processes, and diagnostic marker research in CAS.…”
mentioning
confidence: 99%
“…PM IV (Shriberg et al, 2017c): Question 3. Do findings from cross-sectional and retrospective longitudinal case studies support an ordinal scale of PM scores, termed the Pause Marker Index, to quantify the severity of CAS for research and clinical applications?…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The availability of the several etiologically and demographically diverse databases assembled in the development of the PM and the PMI (see PM IV; Shriberg et al, 2017c) provided the opportunity to address the second of the three questions posed in this series:…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…T he second article in this series (PM II;Shriberg et al, 2017b) described rationale and validity support for a diagnostic marker of childhood apraxia of speech (CAS) termed the pause marker (PM), and a following article (PM IV; Shriberg et al, 2017c) reports validity support for an ordinal severity scale for the PM termed the pause marker index (PMI). The present article assesses the theoretical coherence of the PM with speech processing deficits in CAS.…”
mentioning
confidence: 99%